Estimation of Height Using Body Weight and Segmental Measurements in Children with Cerebral Palsy - Akodu, Olufemi Samuel; Ogunlesi, Tinuade Adetutu; Adekanmbi, Abiodun Folashade (Iranian Journal of Child Neurology, 2023)
Objectives The current study aimed to determine the proxy measurements for height in children with Cerebral Palsy (CP). Materials & Methods In a cross-sectional descriptive study, the length/height of Nigerian children with CP was studied over eighteen months using descriptive statistics. The study subjects comprised children aged 15 months to 17 years with C P. Height/length, weight, arm span, forearm length, mid-upper arm circumference, foot length, head circumference, hip circumference, leg length, and tibia length were measured to the nearest 0.1 cm using standard procedures. The relations between segmental measurements and weight with height were investigated using linear regression. Results A total of 31 children were studied. The correlation between height/ length and other linear measurements has a significantly strong positive relationship. Regression analysis showed that when used singly, the weight and thigh length offered a high explanation for the height variability with little estimation error. On the other hand, weight had a lower mean difference between observed and predicted height (0.21and -0.76, respectively), with thigh length overestimating the height. Conclusion Weight measurement may be the preferred proxy for height in children with C P.